2017
DOI: 10.1007/s40737-017-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Adaptation to First Episode Psychosis Through the Creation of Images

Abstract: This article aims to understand and explore the meaning of adaptation to First Episode Psychosis (FEP). An innovative method of data collection was used with ten participants who experienced FEP which integrated drawings of their lived experience within semi-structured interviews. The data were analysed through Interpretative Phenomenological Analysis and hermeneutic-phenomenological image analysis. Participants' experience was captured in four superordinate themes which identified that adaptation to FEP entai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 47 publications
(94 reference statements)
1
22
0
Order By: Relevance
“…However, ours is the only study to report descriptive statistics on domains and items of the Posttraumatic Growth Inventory among persons having experienced an FEP. Notably, our qualitative findings are consistent with those observed in our review of other studies that, in studying recovery, found positive changes following FEP (4, 42). In explicitly focusing on positive change, our study therefore makes a substantial novel contribution.…”
Section: Discussionsupporting
confidence: 92%
“…However, ours is the only study to report descriptive statistics on domains and items of the Posttraumatic Growth Inventory among persons having experienced an FEP. Notably, our qualitative findings are consistent with those observed in our review of other studies that, in studying recovery, found positive changes following FEP (4, 42). In explicitly focusing on positive change, our study therefore makes a substantial novel contribution.…”
Section: Discussionsupporting
confidence: 92%
“…The first study asked each couple to bring five objects or photos to the interview to remind them of particular times they'd taken MDMA together (Reavey, 2011). The incorporation of visual methods was intended to better reflect the multi-modal nature of reality (Attard, Larkin, Boden & Jackson, 2017;Boden & Eatough, 2014;Reavey, 2011;Reavey & Johnson, 2008;Silver & Reavey, 2010) and focus couples' accounts on specific drug experiences.…”
Section: Data Collectionmentioning
confidence: 99%
“…A quantitative study of 121 people with severe mental illness using community mental health rehabilitation centres in Israel found high levels of trauma,25 and that meaning-making and coping self-efficacy mediated post-traumatic growth experiences 26. Three small (n=7,27 n=7,28 n=1029) qualitative studies using interpretative phenomenological analysis of semi-structured interviews all identified themes of personal growth.…”
Section: Introductionmentioning
confidence: 99%